Peramalan Kebutuhan Air Untuk Penyiapan Lahan Menggunakan Metode Siklis (Studi Kasus Daerah Irigasi Bendungan Batu Bulan Kec.Moyo Hulu) - Hermanto, Koko; Utami, Silvia Firda (UJMC (Unisda Journal of Mathematics and Computer Science), 2019)
Abstract. The area of agriculture in the Moyo Hulu sub-district of Sumbawa Regency is 6000 hectares with irrigation water sources from Batu Bulan Dam, which is the largest dam in Sumbawa Regency with an area of 932 hectares. Considering that Sumbawa Regency is one of the regions with a high level of drought, information on irrigation water requirements for land preparation needs to be known because it can optimize the allocation of the use of dam water discharge. And one of the important stages needed in the planning and management of irrigation systems. Based on this, the aim of this study is to forecast water requirements for land preparation in the irrigation area of Batu Bulan Dam by using cyclical methods because the data patterns are cyclical or seasonal. The factors that influence water requirements for preparing agricultural land are topography, hydrology, climatology and soil texture. From these factors, the data is then analysed so that the volume of water preparation needs to be obtained every month so that the results of the analysis can be predicted for the next period. Keyword: Forecasting, Cyclic methods, water requirements for land preparation, irrigation, agriculture. Abstrak. Luas area pertanian di kecamatan Moyo Hulu Kabupaten Sumbawa sebesar 6000 hektar dengan sumber air irigasi dari Bendungan Batu Bulan yang merupakan bendungan terbesar di Kabupaten Sumbawa dengan luas 932 hektar. Mengingat Kabupaten Sumbawa salah satu wilayah dengan tingkat kekeringan yang cukup tinggi maka Informasi kebutuhan air irigasi untuk penyiapan lahan perlu diketahui karena dapat mengoptimalkan pengalokasian pengunaan debit air bendungan. Serta salah satu tahap penting yang diperlukan dalam perencanaan dan pengelolaan sistem irigasi. Berdasarkan hal tersebut tujuan dari penelitian ini adalah meramalkan kebutuhan air untuk penyiapan lahan di daerah irigasi Bendungan Batu Bulan dengan menngunakan metode siklis karena pola datanya bersifat siklis atau musiman. Adapun faktor-faktor yang mempengaruhi kebutuhan air untuk penyiapan lahan pertanian adalah topografi, hidrologi, klimatologi dan tekstur tanah. Dari data-data faktor tersebut selanjutnya dianalisa sehingga diperoleh volume kebutuhan air penyiapan lahan setiap bulannya sehingga dari hasil analisa tersebut dapat diramalkan untuk periode berikutnya. Keyword: Peramalan, metode Siklis,Kebutuhan air penyiapan lahan, irigasi, pertanian.